Going to America to See the Fens Better? Stephen Gyllenhaal’s Waterland - Sumera, Adam (Text Matters: A Journal of Literature, Theory and Culture, 2015)
Waterland (1992), directed by Stephen Gyllenhaal on the basis of the screenplay by Peter Prince, is a film adaptation of Graham Swift’s novel under the same title, published in 1983. The book could be called unfilmable although the history of cinema knows examples of successful screenings of apparently unfilmable novels, e.g., The French Lieutenant’s Woman. In the case of Swift’s novel, the main potential difficulties could be seen in its wide scope, its intricate mosaic character, and its style.The article analyzes the changes introduced in the adaptation, including the shift of the contemporary action from Greenwich, England to the American city of Pittsburgh. The way of connecting the present with the past by means of “time travel” is discussed. Consequences for possible interpretation resulting from omitting certain elements of the book and introducing new material as well as changing the order of presentation of some of the scenes are shown. Comments on the film are juxtaposed with interpretations of some aspects of the novel taken from key critical texts on Swift’s book. Also specifically cinematic solutions present in Gyllenhaal’s movie are taken into account.